Progress in photoluminescent materials for light-emitting and optoelectronic applications - Moses Kingsford Flomo; Ahmed Olalekan Omoniyi (Next Nanotechnology)
Photoluminescent materials have witnessed substantial advancements in synthesis techniques, structural design, and functional performance, driving innovation across a range of modern applications. Recent research has expanded from traditional rare-earth-doped phosphors to include rare-earth-free sulfides, metal-organic frameworks (MOFs), perovskites, quantum dots (QDs), and carbon-based nanomaterials such as graphene and carbon dots. These materials offer tunable emission properties, high luminescence efficiency, and enhanced stability, making them indispensable in fields such as light-emitting diodes (LEDs), organic LEDs (OLEDs), QDLEDs, bioimaging, diagnostics, fluorescent sensing, and anti-counterfeiting technologies. This review traces the development of photoluminescent materials, beginning with early phosphorescent substances and progressing through the evolution of rare-earth-based systems and emerging alternatives. Emphasis is placed on synthesis methods, emission mechanisms, doping strategies, and structure–property relationships that influence performance. By highlighting key milestones and comparing material classes, this review provides critical insights into the design of next-generation photoluminescent materials. It also outlines current challenges and future prospects for developing cost-effective, high-performance systems tailored for lighting, biomedical, and security-related applications.